Genotype-phenotype correlations in THAP1 dystonia: molecular foundations and description of new cases - LeDoux, Mark S. (2012)
An extensive variety of THAP1 sequence variants have been associated with focal, segmental and generalized dystonia with age of onset ranging from 3 to over 60 years. In previous work, we screened 1,114 subjects with mainly adult-onset primary dystonia (Neurology 2010;74:229-238) and identified 6 missense mutations in THAP1. For this report, we screened 750 additional subjects for mutations in coding regions of THAP1 and interrogated all published descriptions of THAP1 phenotypes (gender, age of onset, anatomical distribution of dystonia, family history and site of onset) to explore the possibility of THAP1 genotype-phenotype correlations and facilitate a deeper understanding of THAP1 pathobiology. We identified 5 additional missense mutations in THAP1 (p.A7D, p.K16E, p.S21C, p.R29Q, and p.I80V). Three of these variants are associated with appendicular tremors, which were an isolated or presenting sign in some of the affected subjects. Abductor laryngeal dystonia and mild blepharospasm can be manifestations of THAP1 mutations in some individuals. Overall, mean age of onset for THAP1 dystonia is 16.8 years and the most common sites of onset are the arm and neck, and the most frequently affected anatomical site is the neck. In addition, over half of patients exhibit either cranial or laryngeal involvement. Protein truncating mutations and missense mutations within the THAP domain of THAP1 tend to manifest at an earlier age and exhibit more extensive anatomical distributions than mutations localized to other regions of THAP1.